Lipase-catalyzed synthesis and characterization of a novel linear polyamidoamine oligomer - Monsalve, Leandro Nicolas (2010)
A linear polyamidoamine oligomer was obtained by polymerization of ethyl acrylate and N-methyl-1,3-diaminopropane, catalyzed by the Candida antarctica lipase. Depending on the reaction conditions such as substrates concentration, solvent and enzyme:substrate ratio, the enzyme catalyzes the polymerization reaction or Michael adducts formation. The polymeric material, characterized by FTIR, 1H and 13C NMR and UV-MALDI-TOF-MS, shows low molecular weight and high monodispersity. The activity showed by C. antarctica lipase in the polymerization reaction is highly selective and allows to obtain a product with potential biomedical applications in mild condition reactions and low environmental impact.